The after-effect of paclobutrazol on morphological characteristics of in vitro Narcissus poeticus ssp. radiiflorus plants - Jevcsák, M.; Ördögh, M.; Jámbor-Benczúr, E. (International Journal of Horticultural Science, 2015)
After different pre-culturing period (12, 23 or 34 days) on ½ MS medium with 1 mg l-1 paclobutrazol, 1 mg l-1 N6-benzyladenine and 0.1 mg l-1 1- naphthaleneacetic acid , 3 groups of Narcissus poeticus ssp. radiiflorus bulb scales were kept on the same medium without hormones. The results were evaluated monthly and the final one happened after 7 month. The best results were achieved due to the shortest pre-culturing period (12 days;  Group 1), with 4.9 bulblets and 4.54% hyperhydricity. The result of the second treatment (pre-culturing period of 23 days; Group 2) was not different significantly but the number of bigger bulblet were higher (4.54 bulblets). After the longest pre-culturing period (34 days; Group 3), the number of bulblets was low (3.68) and more hyperhydricity (18.18%) was detected. The highest number of roots (13.91) was observed in this groupvery likely due to the strong after-effect of paclobutrazol.